Effectiveness Of Technology-Based Business Incubation Programs In Improving Startup Growth - Atika Aini Nasution; Aan Nurhadi; M. Asyari Syahab (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
A business incubator is a forum or institution that aims to foster, guide, and accelerate the growth of start-up businesses by providing resource support such as training, funding, network access, and operational facilities. This study aims to determine the Effectiveness of Technology-Based Business Incubation Programs in Increasing Startup Growth. The method used in this study is a qualitative descriptive approach with literature studies as the main data collection technique. The results of the study indicate that business incubators play an important role in reducing the failure rate of digital startups, increasing competitiveness, and accelerating the commercialization process of digital products and services. An effective incubator is characterized by the ability to provide relevant mentoring programs, mentoring from industry practitioners, and access to funding sources. The conclusion of this study states that the existence of business incubators significantly supports the growth and sustainability of digital startups, but their success still depends heavily on the quality of incubation services and the internal readiness of startups to receive coaching.